RANCANGBANGUN SISTEM DETEKSI FOAM COKE MENGGUNAKAN METODA BACKSCATTER NEUTRON - Rony Djokorayono (BATAN, 2007)
A foam coke detection system has been constructed using backscatter neutron method and has been implemented in oil refinery UP